Village Head Leadership in Increasing Community Participation in Mendik Makmur Village, Longkali District, Paser Regency - Bela Rismayana; Anwar Alaydrus (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The purpose of this study was to find out and analyze the personality characteristics of the village head who is able to provide motivation and input to the community so that there is community participation in Mendik Makmur Village, Longkali District, Paser Regency. This study uses leadership indicators, namely initiative, motivation, coaching, and responsibility as well as to determine the supporting and inhibiting factors in increasing community participation. The data analysis technique used is an interactive model data analysis technique. The results of the study show that in general the leadership of the Mendik Makmur Village Head has carried out its obligations well and always invites the community to participate in village development activities. Then, the village head gave initiatives in the form of suggestions so that the community always innovates to increase productivity, then the motivation given was in the form of encouraging sentences, namely by saying the jargon